GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 22670 species occurrences available in GBIF matching the query: TaxonKey: Populus alba L.. The dataset includes 22670 records from 344 constituent datasets: 1 records from Kremmer Luch. 3 records from Plant (GFEI-PL). 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 1 records from Perchtoldsdorfer Heide. 252 records from Tercer Inventario Forestal Nacional. Ministerio de Agricultura, Alimentación y Medio Ambiente (España/Spain) (IFN3). 4 records from Herbarium, Botany Unit, Finnish Museum of Natural History (H). 1 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 1 records from Deponie Klausdorf. 11 records from Institut Botanic de Barcelona, BC. 1 records from LBV 100 - Artenvielfalt am Rothsee. 1 records from Collection du Musée d'Histoire Naturelle de Nice. 3 records from Ireland's BioBlitz 2012. 1 records from Dornwanger Moos. 26 records from Flora-On: occurrence data of the flora of mainland Portugal. 22 records from Botany Division, Yale Peabody Museum. 1 records from Eppingen und Umgebung. 1 records from Fuchsloch (Mohlsdorf/Ostthüringen). 11 records from Royal Botanical Gardens Herbarium. 111 records from Plant. 2 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 10 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 40 records from Vascular Plant Herbarium, Oslo (O). 10 records from SANT herbarium vascular plants collection. 4 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 3 records from Herbarium de Geo. B. Hinton, México. 1 records from Herbario Museo de La Salle Bogotá (MLS). 1 records from The Erysiphales Collection at the Botanische Staatssammlung München. 2 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1 records from Institut Botanic de Barcelona, BC-Histórico. 6 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 57 records from Missouri Botanical Garden. 21 records from Biological and palaeontological collection and observation data MNHNL. 14 records from Herbario de la Universidad de Almeria. 210 records from FLORIVON. 1 records from Herbarium of University of Białystok - Vascular Plants. 148 records from Carnet en Ligne. 1756 records from Botanical Society of the British Isles - Vascular Plants Database additions since 2000. 1 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 1 records from Instituto de Botánica Darwinion. 3 records from Sistema de apoyo a la toma de decisiones para la reforestación rural en México. 5 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 95 records from Shropshire Ecological Data Network - Shropshire Ecological Data Network Database. 37 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 24 records from IBF Monitoring of Vascular Plants. 1 records from Herbarium of Jyväskylä University Museum. 5 records from inatura - Erlebnis Naturschau Dornbirn. 76 records from Inventaire National du Patrimoine Naturel (I093) : Flore du Massif Armoricain. 28 records from E. C. Smith Herbarium (ACAD). 1 records from Paleobotany Division, Yale Peabody Museum. 2 records from Botanical Information System of Geneva. 3 records from Vascular Plant Collection. 1 records from Roter Berg Werdau (Leubnitz). 1 records from National Trust - Ickworth species data held by The National Trust.. 1 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 2 records from Insect Arthropods (KIDR-IN). 2 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 1 records from UCJEPS TAPIR Provider. 6 records from Herbarium Senckenbergianum (FR). 2 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 22 records from Botanical Society of the British Isles - Changing Flora of Glasgow 1982-2000. 1 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 11 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 41 records from R. L. McGregor Herbarium Vascular Plants Collection. 1 records from Erzental (Oberotterbach). 12 records from New Mexico Biodiversity Collections Consortium database. 6 records from New Zealand Biodiversity Recording Network. 23 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from ALCB - Herbário Alexandre Leal Costa. 1 records from Freiburger Tag der Artenvielfalt. 1 records from Freiburger Netzwerk Artenvielfalt. 2 records from Paleontological collection of the National Museum - Flora. 97 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 2 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 5 records from Canadian Museum of Nature Herbarium. 27 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 2 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 57 records from CONN. 19 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 1 records from Tromsø Museum, Vascular plants. 66 records from Harvard University Herbaria. 2100 records from FlorKart - FlorenKartierung Gefaesspflanzen. 8 records from National System of Protected Areas in Poland - Plants. 57 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 4 records from CIBIO, Alicante:ABH-GBIF. 12 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 12 records from Michigan State University Herbarium Vascular Plants. 19 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 8 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 1 records from Pilstingermoos. 95 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 19 records from CAS Botany (BOT). 1 records from ICN - Herbário do Instituto de Ciências Naturais. 5 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1 records from Herbario de la Universidad de Sevilla, SEV-Historico. 4 records from Plant (JNHM-PL). 1 records from Gemeindegebiet Weikendorf (Marchfeld). 1027 records from Observations du Conservatoire botanique national du Bassin parisien.. 1 records from LaBoOb02. 30 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 5 records from Database Schema for UC Davis [Herbarium Labels]. 1 records from Faberpark (Nürnberg/Stein). 19 records from Botany (UPS). 15 records from Consortium of California Herbaria. 1 records from Lindau im Bodensee. 48 records from Atlas des plantes vasculaires de Lorraine. 1 records from Biologische Station im Kreis Wesel. 5 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 1 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 18 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 2 records from Vascular plant specimens of Akita Prefectural Museum. 1 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 1 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 1 records from Bayerische Donau - Blindheim Donaubrücke. 28 records from BSBI tetrad data for Ireland. 4 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 11 records from Herbario de Universidad de Murcia: MUB. 3 records from Angiosperm specimens of Iwate Prefectural Museum. 10 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1 records from Herbarium of Taiwan Forestry Research Institute. 2 records from University of Alberta Vascular Plant Herbarium (ALTA). 1 records from 3. Tag der Artenvielfalt Hockenheim. 44 records from Green Plant Herbarium (TRT). 20 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 8 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 2 records from Colorado State University Herbarium. 16 records from Biologiezentrum Linz. 4 records from Repatriación de datos del Herbario de Arizona (ARIZ). 5 records from Herbarium Senckenbergianum Görlitz (GLM). 43 records from Lund Botanical Museum (LD). 112 records from Australia's Virtual Herbarium. 7 records from Vascular Plant Herbarium, Trondheim (TRH). 1 records from Isarufer. 27 records from Natural History Museum (London) Collection Specimens. 4 records from Herbarium, Centre for Biodiversity, University of Turku, Finland (TUR). 1 records from renaturierter Main (Kemmern bei Bamberg). 1 records from SMDB - Santa Maria Departamento de Biologia. 22 records from Marie-Victorin Herbarium (MT). 32 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 1 records from Biosphärenpark Wienerwald - Pfaffstätten. 1 records from Wismar Bucht coast-watching. 1170 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 1 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 6 records from MBM - Herbário do Museu Botânico Municipal. 44 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from Herbarium specimens of CBNA (GAP). 1 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 1 records from Trockenhang Greinhartsberg Edelfingen. 1 records from BUND - Dassower See (Lübeck/Dassow). 9 records from Northern Ireland Environment Agency - EHS Species Datasets. 1 records from Mountain Invasion Research Network (MIREN) survey. 3 records from Shire Group of Internal Drainage Boards - Shire Group IDB species data 2004 to present. 299 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 2 records from Precis Plant Data. 36 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 1 records from Bernhardsthal. 4 records from BioFokus. 1 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 515 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 2 records from Herbarium (UNA). 8 records from Jardin botanique de Montréal (JBM). 15 records from VegetWeb - Repositorium von Vegetationsaufnahmen a. 6 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 1 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 193 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 3785 records from Botanical Society of the British Isles - Vascular Plants Database. 13 records from SA Flora (BDBSA). 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 1 records from Birkenpilz. 7 records from Natural History Museum Maastricht (NL) - Herbarium. 7 records from Vascular Plant Herbarium, UiB. 8 records from Herbier de Strasbourg. 1 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 1 records from Artenvielfalt im Beckerbruch (Dessau). 1 records from Universität Salzburg. 1 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 1 records from BÜG. 5 records from Herbarium BSG Vascular Plants. 54 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 1 records from Zukünftiges NSG Höftland/Bockholmwik. 2 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 1 records from Förderzentrum Schmölln. 55 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 10 records from Fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 22 records from The Flora of County Wexford. 67 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 183 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 11 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 1 records from CESJ - Herbário Leopoldo Krieger. 55 records from OEH Atlas of NSW Wildlife. 54 records from Staffordshire Ecological Record - SER Site-based Surveys. 2 records from Freiburger GEO-Tag der Artenvielfalt. 217 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 4 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 9 records from Vascular plants of Amrum 2007-2008. 1 records from Stadtbiotop Ulrichteich. 1 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 4 records from Specimen Database of Colorado Vascular Plants. 21 records from Herbarium of The New York Botanical Garden. 1 records from Projekt Dellbrücker Heide. 27 records from Greater Manchester Ecology Unit - Higher Plant Records From Greater Manchester. 1 records from National Trust - Hatfield Forest species data held by The National Trust.. 1 records from Artenfülle um das Schalkenmehrener Maar. 1 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 19 records from Flore de Franche-Comté. 659 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 1 records from Bolzplatz. 6 records from Staffordshire Ecological Record - SER Species-based Surveys. 29 records from iNaturalist research-grade observations. 2 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 18 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 8 records from SysTax - Botanical Gardens. 3 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 30 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 1 records from IICT Herbário LISC. 1 records from Königstetten. 2 records from University of Lethbridge Herbarium (LEA). 32 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 1 records from Flora of the Stołowe Mts.. 2 records from University of California Museum of Paleontology. 9 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 1 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 1 records from Naturpark Kottenforst-Ville 16.6.09. 319 records from naturgucker. 1 records from MEXU/Flora de Oaxaca. 13 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 19 records from Belgian IFBL Flora Checklists (1939-1971). 48 records from Herbario de la Universidad de Sevilla, SEV. 2 records from Leiner-Herbar Konstanz. 42 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 5 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 6 records from Herbarium Berolinense. 2 records from University of Alberta Museums, Vascular Plant Herbarium. 1 records from Artenbestimmung. 1959 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 3 records from Kathryn Kalmbach Herbarium. 1 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 1 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 1 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 2 records from MEXU/Colección Histórica. 1 records from Carabidae of Poland. 35 records from Herbarium Willing. 1 records from Pottundkopp. 1 records from Mißmahlsche Anlage. 2 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 1 records from WII Herbarium Dataset. 1 records from PRECIS (KwaZulu-Natal Herbarium). 8 records from Natural History Museum, Vienna - Herbarium W. 1 records from Sürther Aue. 2 records from SysTax - Herbaria. 1 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 36 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 1 records from Umgebung der Gesamtschule Winterhude (Hamburg). 1 records from Base de datos para la xiloteca del Instituto de Biología de la UNAM. 10 records from NSW herbarium collection. 1 records from United States National Plant Germplasm System Collection. 2 records from Geographically tagged INSDC sequences. 1 records from Steinbruch Haas Stuttgart-Münster. 2 records from North Ayrshire Countryside Ranger Service - Species within North Ayrshire from 1984 - Present. 1 records from Wangerooge. 2 records from Hortus Botanicus Sollerensis Herbarium (FBonafè). 22 records from Botanical Garden Collection. 7 records from USU-UTC Specimen Database. 2 records from Natural History Museum Rotterdam (NL) - Plantae collection. 23 records from NMNH occurrence DwC-A. 6 records from Louisiana State University Herbarium. 1 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 5 records from University of Vienna, Institute for Botany - Herbarium WU. 39 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 2 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 11 records from PRECIS. 39 records from Tiroler Landesmuseum Ferdinandeum. 354 records from Israel Nature and Parks Authority. 1 records from FUEL - Herbário da Universidade Estadual de Londrina. 2064 records from Dutch Vegetation Database (LVD). 1 records from Gemeinde Sursee. 1 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 3 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 15 records from OAC-BIO Herbarium. 1 records from Mooswald (Freiburg). 3 records from HAS - Herbário Alarich Rudolf Holger Schultz. 1 records from Bergkamen- Bergehalde Großes Holz. 2 records from Utah Valley State College Herbarium. 320 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 2 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 1 records from Irish vascular plant data 1999-2009. 58 records from Naturalis Biodiversity Center (NL) - Botany Wageningen. 39 records from OHN. 197 records from Phytochorologie des départements français. 2 records from Liether Kalkgrube. 281 records from EcoRecord - Vascular plant records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 9 records from MISS_DC_01MAR2006. 2 records from Naturerlebnisraum Koppelsberg. 2 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 1 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 53 records from Phanerogamic Botanical Collections (S). 6 records from California State University, Chico. 1 records from NSG Forst Zinna-Jüterbog-Keilberg. 4 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 1 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 33 records from Jardín Botánico de Córdoba: Herbarium COA. 13 records from Australian National Herbarium (CANB). 21 records from Dataflos. 150 records from Artdata. 1 records from Ibaraki Nature Museum, Vascular Plants collection. 4 records from UA Herbarium. 20 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 8 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 12 records from Biodiversitätsdatenbank des Landes Salzburg. 1 records from Interactive Database of Biodiversity Studies on Terrestrial Arthropod Animals of Korea. 1 records from Luderbusch. 44 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 365 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 49 records from Consortium of California Herbaria. 23 records from Oklahoma Vascular Plants Database Provider. 1 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 455 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 7 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 1 records from Miscellaneous Vascular Plants. 1 records from Grünes Germersheim. 10 records from The Flora of County Waterford. 13 records from Inventario de Flora y Vegetación del Municipio de Enguídanos (Cuenca), 2010. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 1 records from Küstenschutzwald. 1 records from PACA-AGP - Herbarium Anchieta. 36 records from Allan Herbarium (CHR). 1 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 1 records from Schatzinsel Wangerooge. 3 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 34 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 1 records from Steinbruch Mainz-Weisenau, 2. Jahr. 1 records from Tongrube bei Hettstedt. 2 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 2 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 2 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 29 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 17 records from E.C. Smith Herbarium. 1 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 20 records from University of Copenhagen Arboretum. 1 records from Waldsee. 4 records from Online Atlas of vascular plants 2012-2020. 1 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 2 records from Nationaal Herbarium Nederland.
Keywords: GBIF; biodiversity; species occurrences